Microbial Contamination Of Eggshell And Eggs Content Sold In Retail And Fresh Market In Penang - Liaw, Shi Yan (Universiti Sains Malaysia, 2021)
Egg contamination with microorganisms would impact the quality of eggs, which may lead to spoilage and cause intoxication to consumers, posing a public health risk. Contaminated eggs can increase the risk of illness, and this illness can vary from mild symptoms to life-threatening conditions. The purpose of this study was to determine the total microbial load and indicator organisms and identify the species of bacteria isolated from eggshells and egg contents sold in the retail and fresh markets at Penang.